2016
DOI: 10.1186/s13643-016-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities for return-to-work of cancer survivors: time for action—rapid review and expert consultation

Abstract: BackgroundThe spread of early detection and the improvement of cancer treatment have led to an increased prevalence of cancer survivors, including in the working age population. Return-to-work (RTW) of cancer survivors has become a key issue for national cancer control plans. This study aims (1) to identify the factors that have an impact on RTW of cancer survivors and to draw a risk profile supporting health professionals in the screening of those at risk for barriers of RTW and (2) to sharpen these results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 26 publications
8
69
1
3
Order By: Relevance
“…It was the most frequently self‐reported reason for impaired RTW, and fatigue persisting 1.5 years after end of therapy was a significant determinant for impaired RTW in the long run. Our results strengthen findings from previous trials that also found an influence of fatigue on RTW (Kiasuwa Mbengi et al, ; Mehnert, ; Porro et al, ; Wolvers, Leensen, Groeneveld, Frings‐Dresen, & Boer, ). Thus, health professionals' and the public's awareness needs to be raised that fatigue is a serious syndrome (and not just listlessness or moaning) that severely hampers general functioning and daily routine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was the most frequently self‐reported reason for impaired RTW, and fatigue persisting 1.5 years after end of therapy was a significant determinant for impaired RTW in the long run. Our results strengthen findings from previous trials that also found an influence of fatigue on RTW (Kiasuwa Mbengi et al, ; Mehnert, ; Porro et al, ; Wolvers, Leensen, Groeneveld, Frings‐Dresen, & Boer, ). Thus, health professionals' and the public's awareness needs to be raised that fatigue is a serious syndrome (and not just listlessness or moaning) that severely hampers general functioning and daily routine.…”
Section: Discussionsupporting
confidence: 91%
“…Memory and/or attention problems were another frequent selfreported reason for occupational changes, especially among women with no RTW 1 year after surgery (71%). Reduced cognitive ability has been emphasised by several previous studies as reason for impaired RTW but results are ambiguous (Bijker et al, 2017;Kiasuwa Mbengi et al, 2016). Subjective cognitive impairments are a frequently reported adverse effect during adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have argued that training in the use of validated tools for assessing work capacity and for identifying those at risk of problems in RTW is relevant to providers involved in cancer treatment (Egmond, Anema, Singh, van der Beek, & Duijts, 2016;Kiasuwa et al, 2016;Murphy et al, 2016). The RTW intervention was looked upon as either a disturbance or an integrated component of cancer treatment.…”
Section: Implications For Practicementioning
confidence: 99%
“…The provision of workplace support and plans for work accommodation during cancer treatment have shown to facilitate positive RTW outcomes and to enable cancer patients to remain at work (Kiasuwa et al, 2016;Lindbohm et al, 2011;Mehnert et al, 2013;Murphy et al, 2016). Screening of those at risk of encountering difficulties in RTW could help prevent inequality in this respect and could support the awareness of modifiable factors (Kiasuwa et al, 2016). Unfavorable work conditions, which typically affect lowincome and low-level educational jobs, are viewed as some of the factors explaining inequality in RTW (Amir & Brocky, 2009…”
Section: Sebastianmentioning
confidence: 99%